SPIRITUAL MANAJEMEN: SEBUAH REFLEKSI DARI PENGEMBANGAN ILMU MANAJEMEN - Arief, Mohammad (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2010)
Management practise have been long underway, but formal study of knowledge management is relatively new. Initial thought about management theory (Hodgets, 1979) has evolved since Sumarian (3000 BC) in which there is religious doctrine that human sacrifice shown by the God through the exchange of material.This article considers the characteristics of the development of management science based on the spiritual aspect. Perspective of spirituality is very interesting to study because at present the development of management theory has moved towards the practises that emphasize the values of culture. The values of culture held by individuals will control the behavior and further change the status of a worship. Thus, the values of culture will be strengthen individual spirituality which owned, so it can create an organization competitive advantage.